Detect the Levels of Some Cytokines in Women Infected With Human Papillomavirus in Kirkuk City - Mohammed, Asmaa Jamal; Saleh Alhammadi, Wijdan Abdulghani; Salih, Zobaida Mahmood; Mohammed, Parzhin Sardar (American Journal of Biodiversity, 2025)
Background & aim: The most frequent cause of cutaneous warts and mucosal papillomas is the human papillomavirus (HPV), and high-risk strains of the virus are linked to the development of colorectal, genital, and oropharyngeal cancers. Therefore, the current study aims to detect the levels of some physiological parameters and cytokines in women infected with human papillomavirus. Materials & methods: The study was conducted at the Department of Biology, College of Sciences, University of Kirkuk. The sample included (240) Iraqi women patients with cervical diseases who attended Kirkuk Teaching Hospital and private clinical in Kirkuk City from February to June 2025. Results: by using ELISA, it was found that the number of infected women was 37 (15.4%) out of a total of 240. The highest infection rate was found in the 20-30 age group, reaching 51.4%, while the lowest infection rate was in the 41-50 age group, reaching 13.5%. The average age of women was 33.7±13.29. The findings exhibited the levels of some cytokines in HVP patients and healthy women, where IL-10 levels in serum of HVP patients (2.93 ±0.46) demonstrated significant (P<0.05) elevated compared with control women (1.84 ±0.17). the levels of IL-17 exhibited a significant (P<0.05) elevated in HVP patients (254.3 ±25.91) compared with healthy women (165.1±15.08). the levels of tumor necrosis factor α (TNF-α) exhibited significant (P <0.05) elevated in HVP patients (3.04±0.53) compared with healthy women (1.63±0.21). Conclusions: The younger women are more susceptible to HPV infection than other age groups, and that HPV infection directly affects the levels of certain cytokines that play an important role in infection.